Bioactive isoflavones from Pueraria lobata root and starch: Different extraction techniques and carbonic anhydrase inhibition. (February 2018) - Mocan, Andrei; Carradori, Simone; Locatelli, Marcello; Secci, Daniela; Cesa, Stefania; Mollica, Adriano; Riga, Simona; Angeli, Andrea; Supuran, Claudiu T.; Celia, Christian; Di Marzio, Luisa
Abstract: Kudzu, the dried root of an important edible plant ( Pueraria lobata ), is used in Traditional Chinese Medicine for the important nutritional value strictly related to its isoflavone derivatives. These compounds characterize the quality of kudzu contained in different preparations, as pharmaceutical ingredient as well as dietary/food supplement (e.g. starch). The optimization of the isoflavones recovery, monitored by HPLC-PDA, through different innovative and conventional extraction techniques, e.g. microwave-assisted, ultrasound-assisted and conventional extraction, represented a suitable challenge in food industry and natural products evaluation. The impact on the isoflavone extraction by using an ionic liquid-assisted procedure was also considered. Furthermore, the inhibitory activity of the most representative isoflavones, isolated from kudzu, was evaluated using four isoforms (I, II, IX and XII) of human carbonic anhydrase (hCA) due to their role in several physiopathological processes. Graphical abstract: Image 1 Highlights: P. lobata root and starch were extracted using various innovative techniques. Isoflavone content was detected using a validated HPLC-PDA method. 1-Butyl-3-methylimidazolium bromide enhanced the isoflavone extraction. Evaluation of inhibitory activity of isoflavones against hCA IX and XII isoforms.